(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
The study of morphological changes in lymph nodes in patients after emergency nephrectomy is one of the important scientific and practical tasks in medicine today. Nephrectomy is a surgical procedure performed due to tumors and other formations, chronic renal failure and other pathologies, which can lead to changes in the immune system. This is likely to manifest itself in reactive and pathological changes in lymphoid tissues, and lymph nodes play a key role in immune control, as well as participate in the formation of tumor and inflammatory reactions. Thus, the study of the morphology of lymph nodes after emergency nephrectomy is scientifically and clinically important, it helps to identify pathogenetic mechanisms of adaptation of the organism, to determine diagnostic and prognostic criteria, as well as to optimize treatment and rehabilitation methods.